Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1029/2004pa001031
|View full text |Cite
|
Sign up to set email alerts
|

A solar (irradiance) trigger for millennial‐scale abrupt changes in the southwest monsoon?

Abstract: [1] Marine sedimentary records of the last glacial from tropical monsoon latitudes indicate climate fluctuations comparable to rapid changes in d 18O recorded in Greenland. Synchronizing two high-resolution sedimentary records from the Oman and Pakistan margins, we resolve millennial-scale reversals in sea surface temperature (SST) gradient (DSST) across the Arabian Sea which directly correspond with the majority of DansgaardOeschger (D-O) events for the last 65 kyr. The relative amplitude of individual monsoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 107 publications
(170 reference statements)
4
35
0
Order By: Relevance
“…These results add to a growing body of evidence of alkenone and foraminiferal abundance derived SST estimates implying 83 that SSTs in the Arabian Sea were 2 -4°C cooler than present at the LGM (Emeis et al, 1995;Bard et al, 1997;Rostek et al, 1997;Sonzogni et al, 1998;Cayre and Bard, 1999;Higginson et al, 2004;Naidu and Malmgren, 2005).…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…These results add to a growing body of evidence of alkenone and foraminiferal abundance derived SST estimates implying 83 that SSTs in the Arabian Sea were 2 -4°C cooler than present at the LGM (Emeis et al, 1995;Bard et al, 1997;Rostek et al, 1997;Sonzogni et al, 1998;Cayre and Bard, 1999;Higginson et al, 2004;Naidu and Malmgren, 2005).…”
Section: Discussionsupporting
confidence: 53%
“…Since then, a number of investigations employing the use of alkenones (Emeis et al, 1995;Bard et al, 1997;Rostek et al, 1997;Sonzogni et al, 1998;Higginson et al, 2004) and foraminiferal abundances (Cayre and Bard, 1999;Naidu and Malmgren, 2005) have suggested that LGM SSTs were in fact on the order of 3°C cooler than present. With the exception of Sonzogni et al (1998), these studies have utilized a time series approach, thus giving a temporal, rather than spatial, history of SST.…”
Section: Lgm Comparison With Alkenone and Transfer Function Datamentioning
confidence: 99%
See 3 more Smart Citations